Educational intervention on Oro-dental Hygiene among Secondary School Children at Dhaka, Bangladesh (City Dental College Journal, 2013)
Aim: An intervention study was conducted on oro-dental hygiene among secondary school students in a specific school at Dhamrai, Dhaka of Bangladesh. The main objective was to assess knowledge on oro-dental hygiene among secondary school student and also carry out an evaluation of health education intervention program. Methods: This was a quasi-experimental study. Specific health information messages on oro-dental hygiene were disseminated to 64 students of Kailash Chandra high school at Dhamrai through a group approach using posters, flip charts and dental models. Results: It was observed that 80% of the students heard about the importance of oro-dental hygiene before intervention and that reached to 100% after intervention. Before intervention, 51.7% possessed correct knowledge about oro-dental care and that increased up to 90% after intervention. It was also observed that only 46.7% of the participants knew about the health hazards as consequences of not tooth brushing and it rose up to 80% after intervention. Conclusion: The study disclosed the status of knowledge and practice which greatly improved after dental health educational intervention program. Therefore, the intervention program through child to child education had been found effective in this study. DOI: http://dx.doi.org/10.3329/cdcj.v10i2.16318 City Dent. Coll. J Volume-10, Number-2, July-2013